UMA METODOLOGIA PARA A INTEGRAÇÃO DE APLICAÇÕES EMPRESARIAIS COM WEB SERVICES USANDO MDA - VALE, Samyr Beliche (2004)
This paper presents a methodology for integrating business applications with Web services through the creation of meta-models in MDA. This methodology covers steps for the integration process and presents an architecture based on semantic middlware to integrate legacy applications.